The incorporation of zinc oxide quantum dots as photoanode for dye-sensitized solar cells - Zainol Abidin, Yasmin (2022)
O'Regan and Gratzel introduced a new type of solar cell based on plant photosynthesis in 1991 known as DSSC, which is widely studied due to its low fabrication cost, secure and reliable energy supply. DSSC describes the components of a solar cell as well as the energy conversion process that also can utilising nanotechnology. The semiconducting material ZnO QDs was chosen in search of a photoanode material for DSSC as an up-and-coming photovoltaic technology for next-generation solar cells. ZnO has the most diverse range of nanostructures and high bulk electron mobility. Theoretically, the combination of ZnO and QDs of properties opens up a lot of DSSC options available while the features of QDs light-harvesting materials such as high absorption coefficient, multiple exciton generation possibilities, and easily tuneable absorption range that can deliver low production costs. TiO2 is the conventional electron transport material used in DSSC incurs high temperature processing in synthesis and has almost the same bandgap as ZnO. However, ZnO has higher bulk electron mobility than that of TiO2, resulting in faster bulk electron transport in a ZnO photoanode, which may lead to efficient electron extraction. ZnO also has good electrical conductivity and better exciton binding capacity at room temperature. Other metal oxide structures may have room for development, as improved electron transport properties could alleviate mass transport limitations. In this research, ZnO QDs were synthesized using a self-assembly method with low-temperature processing (60-65 °C). The thin films of ZnO QDs were deposited on glass using the spin coating method with different parameters: time, speed and number of steps. The thin film of ZnO QDs were characterized using FESEM, XRD and UV-vis to study the morphology, crystallinity and absorption. The FESEM pictures revealed the morphology structure of five layers 500°C has spherically shaped ZnO nanoparticles with average diameters of QDs varied between 13.5 nm and 32.1 nm. From the XRD analysis, at the diffraction peak at (101) was the maximum intensity and it can be concluded that the crystallite size evolution was attributed to higher mobility at higher temperature (500 °C) with average diameter of around 15.72 nm. The UV-VIS absorption spectrum showed excitonic absorption peak at 282 nm demonstrates the synthesis of the high optical quality of ZnO QDs. The optical bandgap was calculated from the Tauc’s plot as 4.01 eV where the bandgap value was higher than the bandgap of bulk ZnO which indicates the formation of ZnO QDs as photoanode. ZnO QDs indicate the adsorption on the photoanode to facilitate electron transport in the will still be of particular interest as photoanode material in DSSCs. The performance of DSSC based on ZnO QDs as photoanode by spin coating of ZnO QDs with varying the number of spin coating layers and annealing temperatures at 300, 400, and 500 °C were evaluated. ZnO QDs based DSSC achieved highest efficiency of ±0.0056% and a Voc of 0.13990 V on the device with 5 layers of spin coating and annealed at 500°C.